Pertanggungjawaban Pidana Korporasi Di Bidang Perpajakan (Studi Kasus Putusan Mahkamah Agung Nomor : 2239 K/PID.SUS/2012) - Arief Dwiatmoko; Bambang Surojo (SAPIENTIA ET VIRTUS, 2015)
Tax collection system by using the self-assessment system has been used by the taxpayer "mischievous" to shrink the tax value or even do not want to pay the tax. For example the case of criminal offenses committed by corporate taxpayer that occur over fourteen companies belonging to the company Asian Agri Group (AAG), which was undermining the value of the tax to take advantage of his company. The conclusion from this study is that the criminal act committed by fourteen companies belonging to the company Asian Agri Group (AAG) is a criminal offense in the field of corporate taxation. Based on the Strict Liabilility Concept and Vicarious Liability Concept, then the corporation can be sentenced to criminal penalties in accordance with the provisions of Article 39 paragraph (1) of the Taxation Law and criminal penalties in accordance with the provisions of Article 43 paragraph (1) of the Taxation Law for the leaders of each of the corporation who participated or helped commit a criminal act in the field of taxation.